Pengaruh Penggunaan Probiotik Mina Pro Dosis yang Berbeda terhadap Pertumbuhan Berat Mutlak Benih Lele Mutiara (Clarias gariepinus) Ukuran 5-7 cm di Bak Pemeliharaan - Gigih Sugianto; Maria Agustini; Indra Wirawan (Zebra: Jurnal Ilmu Peternakan dan Ilmu Hewani, 2025)
One of the problems of catfish cultivation (Clarias gariepinus) that can hinder this cultivation business is the slow growth of fish weight. The purpose of this study is to determine the effect of different administration of Mina Pro probiotics on the absolute weight growth of pearl catfish seeds measuring 5-7 cm in the maintenance tub. The method used in this study is an experimental method. The design used in this study was a Complete Randomized Design (RAL) with four treatments and six replicates. The treatment given is: addition of probiotics mina pro at a dose of 2 ml/kg of feed, 4 ml/kg of feed, 6 ml/kg of feed and without the addition of probiotics to feed. Other parameters that were also studied included water quality including temperature, pH and DO.